2021
DOI: 10.1038/s41420-021-00439-7
|View full text |Cite
|
Sign up to set email alerts
|

Human pluripotent stem cell-derived alveolar organoids for modeling pulmonary fibrosis and drug testing

Abstract: Detailed understanding of the pathogenesis and development of effective therapies for pulmonary fibrosis (PF) have been hampered by lack of in vitro human models that recapitulate disease pathophysiology. In this study, we generated alveolar organoids (AOs) derived from human pluripotent stem cells (hPSCs) for use as an PF model and for drug efficacy evaluation. Stepwise direct differentiation of hPSCs into alveolar epithelial cells by mimicking developmental cues in a temporally controlled manner was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 40 publications
1
44
0
Order By: Relevance
“…In addition, knockout of mfge8 gene exaggerated pancreatic fibrosis after repeated cerulein injection in mice. These results were consistent with several other studies, which also showed that MFG-E8 has anti-fibrotic effects (Brissette et al, 2016;Fujiwara et al, 2019;Shi et al, 2020;Kim et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, knockout of mfge8 gene exaggerated pancreatic fibrosis after repeated cerulein injection in mice. These results were consistent with several other studies, which also showed that MFG-E8 has anti-fibrotic effects (Brissette et al, 2016;Fujiwara et al, 2019;Shi et al, 2020;Kim et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, hiPSC-derived models are considered suitable for drug safety evaluation. A recent study showed that TGF-β1 induced fibrosis in the organoid from hiPSCs provided alveolar epithelial cell type 1 cells (AT1), ATII, and mesenchymal cells (Kim et al, 2021). Future studies should examine suitable endpoints to detect drug-induced fibrosis using in vitro models.…”
Section: Discussionmentioning
confidence: 99%
“…FGF7, FGF10, Wnt/β-catenin, and BMP inhibitors are added to lung organoid media [ 19 , 25 ]. In addition, EGF and inhibitors of TGF-β can be added for organoid size control and suppression of epithelial–mesenchymal transition (EMT), respectively [ 26 ]. To prevent anoikis of single cells and increase the cell survival, the ROCK inhibitor, Y-27632, is also used for several days after the initial seeding or passage ( Table 1 ).…”
Section: Lung Organoidsmentioning
confidence: 99%